A cellular-centric service architecture for machine-to-machine (M2M) communications - Lo, Anthony; Yee Law; Jacobsson, Martin (IEEE wireless communications, 2013)
A machine-to-machine (M2M) communications system is a large-scale network with diverse applications and a massive number of interconnected heterogeneous machines (e.g., sensors, vending machines and vehicles). Cellular wireless technologies will be a potential candidate for providing the last mile M2M connectivity. Thus, the Third Generation Partnership Project (3GPP) and IEEE 802.16p, have both specified an overall cellular M2M reference architecture. The European Telecommunications Standards Institute (ETSI), in contrast, has defined a service- oriented M2M architecture. This article reviews and compares the three architectures. As a result, the 3GPP and 802.16p M2M architectures, which are functionally equivalent, complement the ETSI one. Therefore, we propose to combine the ETSI and 3GPP architectures, yielding a cellular-centric M2M service architecture. Our proposed architecture advocates the use of M2M relay nodes as a data concentrator. The M2M relay implements a tunnel-based aggregation scheme which coalesces data from several machines destined to the same tunnel exit-point. The aggregation scheme is also employed at the M2M gateway and the cellular base station. Numerical results show a significant reduction in protocol overheads as compared to not using aggregation at the expense of packet delay. However, the delay rapidly decreases with increasing machine density.